The “Evil Inclination” of the Jews: The Syriac Yatsra in Narsai’s Metrical Homilies for Lent - Becker, Adam H. (The Jewish quarterly review, 2016)
The yetser ha-ra‘ (“the evil inclination”) has become a standard part of traditional Jewish psychology. This rabbinic expression has its roots in the Second Temple period but ultimately derives from certain passages in the Hebrew Bible. Until now the comparable Christian Aramaic evidence for this term has general been ignored. The fifth-century Syriac author, Narsai, develops a theory of the “evil inclination” (yatsra bisha) in his homilies on moral rebuke, particularly those addressed to his audience during Lent. For Narsai the unruliness of the yatsra derives from envy, a vice which is the fundamental characteristic of Satan, the socially divisive “hater of the human being.” This article describes the origins of the Syriac term, yatsra, from the Hebrew yetser and then examines Narsai’s understanding of the yatsra, setting it within its cultural context and then relating it to the notion of the yetser ha-ra‘ within the Babylonian Talmud.